Effective Assessment: A Challenge to Succesful Implementation of Performance Lag Address Programme. The Case of Primary Schools in Gutu North Zvavahera Cluster of Zimbabwe. - Masomera, Samuel; Ganga, Emily (Advances in Social Sciences Research Journal, 2015)
The Performance Lag Address Prgramme(PLAP) is a teaching strategy aimed at addressing gaps and challenges of learners in mastering concepts being taught by initially going back to their last point of success.Low academic pass rate in primary and secondary schools influenced researchers and academics to come up with a strategy which specifically address individual challenges of learners and enhance academic performance through individualised instruction.However,effective assessment continues to be a challenge to many teachers.The research sought to investigate the the problems posed by the lack of effective assessment of the implementation of PLAP.The study was conducted in Gutu North Zvavahera Cluster involving 25 particpants from six schools.Data was collected through indepth interviews, focus group discussions and document analysis of teachers’ PLAP record books to complement findings from interviews and FGDs.The found oput that effective assessment is a challenge in the effective implementation of PLAP.The Wide Range Achievement Test was criticised of not giving teachers adequate insight on the real problems facing learners.Teachers highlighted that they are not fully equipped and lack required btechinical know how of using various assessment methods beside tests. The recommended format of recording PLAP was seen to be vague assessment and communicating elaborately the performance of the learners.The researchers recommended tha the edcuation system should prioritise assessment as a major component of the teaching and learning process by providing skills and material support to teachers.District offices should have expert teachers on effective assessmnet who help teachers in using multiple assessment methods and realise the benefit of doing so.